2017
DOI: 10.1159/000480063
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Squash and Touch Preparation Cytology of Brain Lesions Stained with H+E and Diff-Quik™: A 20-Year Retrospective Analysis and Comparative Literature Review

Abstract: Objective: Squash preparation (SP) is a rapid technique for the intraoperative assessment of brain lesions. Only a few studies have employed touch preparation (TP) cytology and Diff-QuikTM (DQ) staining in conjunction with SP. Our study aimed to assess the diagnostic efficacy of SP of brain lesions at our institution, ascertain the additional effect of TP and DQ staining, examine factors affecting the sensitivity and specificity of our methods, and compare our findings with those of previous investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
6
1
Order By: Relevance
“…Generally, TIC is considered acceptable for the rapid diagnosis of brain tumors when compared to histological diagnosis [1,11]. Although a previous report examined the diagnostic concordance rate from the tumor, the present study showed 100% concordance at the macroscopical tumor, with 92.9% of specimens being determined to be A1.…”
Section: Discussioncontrasting
confidence: 55%
“…Generally, TIC is considered acceptable for the rapid diagnosis of brain tumors when compared to histological diagnosis [1,11]. Although a previous report examined the diagnostic concordance rate from the tumor, the present study showed 100% concordance at the macroscopical tumor, with 92.9% of specimens being determined to be A1.…”
Section: Discussioncontrasting
confidence: 55%
“…For brain tumors in people, major limitations of squash prep cytology are encountered with firm and tough or extensively necrotizing lesions that led to inadequate samples. 27 In the present study, an inadequate sample rate was not calculated. However, it is the authors' opinion that bladder carcinomas tend to be friable and suitable for squash prep cytology in almost all cases.…”
Section: Discussionmentioning
confidence: 82%
“…Squash prep cytology has already been reported to be useful in diagnosing nervous system, 22 nasal cavity, 23,24 and gastric lesions 21 in dogs. In people, squash prep cytology is mainly used to intraoperatively diagnose brain lesions, 27 demonstrating high sensitivity, specificity, and overall diagnostic accuracy. For brain tumors in people, major limitations of squash prep cytology are encountered with firm and tough or extensively necrotizing lesions that led to inadequate samples 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is customary in most laboratories to use the smear and frozen section techniques to complement each other, pathologists with lacking experience in cytology may be reluctant to prepare smears. However, pathologists should be aware that a better cellular detail without freezing artifacts can be obtained with the smear technique [16][17][18].…”
Section: Discussionmentioning
confidence: 99%